2020
DOI: 10.21615/cesp.13.2.6
|View full text |Cite
|
Sign up to set email alerts
|

La construcción de producciones orales en la infancia a partir de imágenes realistas y no realistas

Abstract: La construcción de producciones orales en la infancia a partir de imágenes realistas y no realistas. Rev. CES Psico, 13(2), 85-101.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Narratives required the integration of data and the justification of the storyline in response to questions. It was observed that less realistic pictures allowed children to construct narratives (see Mareovich et al, 2020). These narrative productions exhibited a higher frequency of argumentative episodes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Narratives required the integration of data and the justification of the storyline in response to questions. It was observed that less realistic pictures allowed children to construct narratives (see Mareovich et al, 2020). These narrative productions exhibited a higher frequency of argumentative episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptions involve the presentation of elements depicted in pictures, while narratives encompass both verbal components (e.g., the use of causal and temporal conjunctions) and non-verbal cognitive skills (e.g., inference and identification of key concepts), as established by prior research (e.g., Berman & Katzenberger, 2004;Shapiro & Hudson, 1991). The A previous study showed that children tend to produce narratives when presented with unrealistic pictures during interaction, while more realistic images promote the generation of descriptions (Mareovich et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations